Half-Life of Serum Elimination of Perfluorooctanesulfonate, Perfluorohexanesulfonate, and Perfluorooctanoate in Retired Fluorochemical Production Workers - Olsen, Geary W.; Burris, Jean M.; David J. Ehresman; John W. Froehlich; Andrew M. Seacat; Butenhoff, John L.; Zobel, Larry R. (Environmental health perspectives, 2007)
Background: The presence of perfluorooctanesulfonate (PFOS), perfluorohexanesulfonate (PFHS), and perfluorooctanoate (PFOA) has been reported in humans and wildlife. Pharmacokinetic differences have been observed in laboratory animals. Objective: The purpose of this observational study was to estimate the elimination half-life of PFOS, PFHS, and PFOA from human serum. Methods: Twenty-six (24 male, 2 female) retired fluorochemical production workers, with no additional occupational exposure, had periodic blood samples collected over 5 years, with serum stored in plastic vials at$-80° C$. At the end of the study, we used HPLC-mass spectrometry to analyze the samples, with quantification based on the ion ratios for PFOS and PFHS and the internal standard$^{18}O_2-PFOS$. For PFOA, quantitation was based on the internal standard$^{13}C_2-PFOA$. Results: The arithmetic mean initial serum concentrations were as follows: PFOS, 799 ng/mL (range, 145-3,490); PFHS, 290 ng/mL (range, 16-1,295); and PFOA, 691 ng/mL (range, 72-5,100). For each of the 26 subjects, the elimination appeared linear on a semi-log plot of concentration versus time; therefore, we used a first-order model for estimation. The arithmetic and geometric mean half-lives of serum elimination, respectively, were 5.4 years [95% confidence interval (CI), 3.9-6.9] and 4.8 years (95% CI, 4.0-5.8) for PFOS; 8.5 years (95% CI, 6.4-10.6) and 7.3 years (95% CI, 5.8-9.2) for PFHS; and 3.8 years (95% CI, 3.1-4.4) and 3.5 years (95% CI, 3.0-4.1) for PFOA. Conclusions: Based on these data, humans appear to have a long half-life of serum elimination of PFOS, PFHS, and PFOA. Differences in species-specific pharmacokinetics may be due, in part, to a saturable renal resorption process.